Diffuse Interstitial Lung Disease in Patients with Microscopic Polyangiitis: Clinical Case and Literature Review (Revista de Medicina Clinica, 2022)
Microscopic polyangiitis (MPA) is a systemic disease classified as a vasculitis with small vessel involvement, and it usually expresses anti-neutrophil cytoplasmic antibodies (ANCA), normally related to anti-myeloperoxidase antibodies (MPO). We present a clinical case of a 73-year-old patient with diffuse interstitial lung disease with a radiological pattern of usual interstitial pneumonia. It had more than 10 years of development without diagnostic affiliation. Suddenly, the patient suffered from acute renal failure, with positive MPO-ANCA. Kidney and pulmonary biopsy was compatible with microscopic polyangiitis.
Keywords: Microscopic polyangiitis; Interstitial lung disease; Usual interstitial pneumonia